From the pseudo-cleft to the the-N-is construction in spoken English: the birth of a new paradigm - Florine Berthe (Anglophonia)
Traditionally, the pseudo-cleft construction is studied alongside the cleft construction as a focalisation marker and a syntactic restructuring device (Khalifa, 2004; Weinert and Miller, 1996). A study of the pseudo-cleft in spoken English shows that the construction differs significantly from the cleft construction and that it should be analysed alongside markers such as the thing is or other variants of this lexico-grammatical pattern. This article puts forward three linguistic properties shared by the two constructions which demonstrate the need for a simultaneous study of the pseudo-cleft construction and the the-N-is construction in spoken English. The article first deals with the syntactic organisation of the two constructions. While the pseudo-cleft construction has long been described as displaying different degrees of syntactic integration in spoken English (Weinert and Miller, 1996; Auer, 2009; Gaudy-Campbell et al., 2016), the the-N-is construction is generally associated with a loosely integrated syntactic structure. This article will show that the least prototypical instances of the the-N-is construction also exhibit stronger degrees of syntactic integration. The focus is then on the co-textual dependency displayed by these constructions. A corpus study shows that both constructions can derive from the previous discourse, in which case the initial part of the structure conveys old information. The construction may also be co-textually independent and convey presupposed information that signals no direct link to the previous discourse. Finally, the article is concerned with the prosodic pattern of these constructions. Using Herment and Leonarduzzi’s (2015) work on the pseudo-cleft construction as a point of comparison, this article will show that the the-N-is construction exhibits similar prosodic patterns which tend to occur with comparable contextual parameters.